2019
DOI: 10.1016/j.jhep.2019.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Tick-tock hedgehog-mutual crosstalk with liver circadian clock promotes liver steatosis

Abstract: Steatosis GLI code? Highlights Hh signaling shows diurnal oscillations in liver and hepatocytes in vitro and in vivo. Hh signaling feeds-back on the liver clock via GLI transcription factors. The amplitude of the oscillations of the liver clock is decreased in hepatocytes from Smo-knockout mice. Rhythmicity of many metabolic pathways, including hepatic lipid metabolism, is affected by oscillating Hh signaling. Diurnal timing of starvation affects the clock-hedgehog module differently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Several Hh pathway genes (Ihh, Ptch1, Smo, Hhip1, Fu, SuFu) showed circadian fluctuations in the liver and hepatocytes in vitro, the genes encoding Gli transcription factors (Gli1, Gli3) exhibited only tiny fluctuations and the serum levels of Indian, the ligand encoded by Ihh, oscillated with 24-hour periodicity. 15 Bmal1 downregulation in hepatocytes provoked important alterations in the expression of Hh pathway genes (upregulation of Gli1 and Ihh, downregulation of Ptch1) and, in turn, altered expression of clock genes in SAC-KO mice was demonstrated and corroborated in vitro using RNA interference against Gli1 and Gli3. Rhythmicity of many metabolic pathways, including hepatic lipid metabolism, was affected by Smo knockout in SAC-KO hepatocytes, as evidenced using genome-wide screening.…”
Section: See Article Pages 1192-1202mentioning
confidence: 84%
See 2 more Smart Citations
“…Several Hh pathway genes (Ihh, Ptch1, Smo, Hhip1, Fu, SuFu) showed circadian fluctuations in the liver and hepatocytes in vitro, the genes encoding Gli transcription factors (Gli1, Gli3) exhibited only tiny fluctuations and the serum levels of Indian, the ligand encoded by Ihh, oscillated with 24-hour periodicity. 15 Bmal1 downregulation in hepatocytes provoked important alterations in the expression of Hh pathway genes (upregulation of Gli1 and Ihh, downregulation of Ptch1) and, in turn, altered expression of clock genes in SAC-KO mice was demonstrated and corroborated in vitro using RNA interference against Gli1 and Gli3. Rhythmicity of many metabolic pathways, including hepatic lipid metabolism, was affected by Smo knockout in SAC-KO hepatocytes, as evidenced using genome-wide screening.…”
Section: See Article Pages 1192-1202mentioning
confidence: 84%
“…Rhythmicity of many metabolic pathways, including hepatic lipid metabolism, was affected by Smo knockout in SAC-KO hepatocytes, as evidenced using genome-wide screening. 15 Interestingly, nutritional challenge represented by high-fat diet or starvation applied at diverse zeitgeber time differently impacted the biological clock-Hh signaling interplay and these results could supply a mechanistic explanation for the dissimilar effect of differently timed eating/fasting on the liver.…”
Section: See Article Pages 1192-1202mentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, specifically in hepatocytes, we recently found that Gli1 is part of a Gli-network and behaves different than in other cell types [25]. Furthermore, it is known that the expression of both genes is subject to pronounced diurnal oscillation [11]. Thus, measurements at a single time point may not be the best choice for estimating Hh pathway activity.…”
Section: Hh/mtor Crosstalk Influences Mitochondrial Metabolism and Thmentioning
confidence: 99%
“…Although the molecular mechanisms driving the regulation of metabolic processes via mTOR signalling are well understood in principle, there are still major gaps in the research on the crosstalk of mTOR with signalling pathways known to serve as gatekeepers for lipid metabolism in the liver. Recently, we discovered that the Hedgehog (Hh) pathway is an essential player in liver lipid metabolism and metabolic zonation, influencing circadian rhythms [9][10][11]. The Hh pathway can be induced by binding of the Hh ligands Indian Hh, Sonic Hh and Dessert Hh to the receptors Patched (PTCH).…”
Section: Introductionmentioning
confidence: 99%